STUDIES ON THE CHEMICAL COMPOSITION OF DENTAL ENAMEL DURING PROFESSIONAL BLEACHING WITH CARBAMIDE PEROXIDE COMPLEX - Tkachenko, I.M.; Lemeshko, A.V.; Brailko, N.N.; Kovalenko, V.V.; Shundryk, M.A. (World of Medicine and Biology, 2020)
This study examined changes in the chemical composition of the tooth enamel surface during the professional hygiene and the use of carbamide peroxide complex as a chemical component of the clinical teeth bleaching system. Because of the performed studies, we found a difference in carbon levels with changes in values from 40.03 on the untreated surface to 0.87, when using 44 % carbamide peroxide-based bleaching agents. There were also changes in the oxygen amount from 25.24 to 0.44, sodium content from 0.46 to 0.02, a decrease in the phosphorus amount from 11.32 to 0.3 and a significant calcium content decrease from 18.4 to 0.52. We also observed a decrease in the nitrogen amount from 2.4 to 0.27 and in the magnesium content – from 0.05 to 0.008. Changes in these indices will significantly affect changes in the values of the oral cavity indices and clinical manifestations, which in turn will depend on the characteristics of functional and structural resistance of enamel.